When public interest meets private profit: The principle of proportionality in Indonesian PPP contracts - Lubis, Diana Febrina; Hernoko, Agus Yudha; Purba, Hasim; Harianto, Dedi (International Journal of Innovative Research and Scientific Studies, 2025)
Public-private partnership (PPP) contracts in Indonesia are designed to accelerate infrastructure development by mobilizing private financing and expertise. However, they often raise concerns regarding fairness when private profits outweigh public interests. This study examines the implementation of the principle of proportionality as a legal safeguard to balance rights, obligations, risks, and benefits within PPP contracts. Using a normative-empirical approach, the research analyzes statutory frameworks such as Presidential Regulation No. 38 of 2015, doctrinal insights from proportionality and contractual balance theories, and qualitative data from interviews with government officials, state-owned enterprises, legal experts, and community representatives. Case studies of projects such as Palapa Ring, Umbulan Water Supply, Kertajati Airport, Jakarta-Bandung High-Speed Railways (Whoosh), Cisumdawu Toll Road, and the Balikpapan–Samarinda Toll Road illustrate how proportionality operates in practice through mechanisms such as risk allocation, Viability Gap Fund, and Availability Payment schemes. The findings indicate that Indonesia has institutionalized proportionality to some extent—particularly through standardized risk-sharing and government support—yet significant challenges remain, including tariff fairness, demand risk, and regulatory clarity. The study concludes that proportionality is not merely a doctrinal principle but a practical requirement for achieving equitable PPP contracts. Ensuring proportionality enhances public trust, protects vulnerable groups, and sustains investor confidence, ultimately reconciling private profit with public welfare in infrastructure partnerships.